The Influence of Implicit Advertising D'Alba Spray Serum's Implicit Based Soft Selling Strategy on Generation Z's Interest in Buying Skincare Products in Padang City - Adinda Fitri Nabila; Abror Abror (STIE Amkop Makassar, 2026)
The development of social media has changed the pattern of marketing communication, one of which is through a soft selling strategy based on implicit advertising that displays products subtly as part of the audience's content, lifestyle, and daily experience. This study aims to analyze the influence of soft selling strategies based on implicit advertising d'Alba Spray Serum on the buying interest of Generation Z in Padang City, with lifestyle and brand image as mediating variables. This study uses an associative quantitative approach with a sample of 174 Generation Z respondents in Padang City who were selected through purposive sampling techniques, namely respondents who actively use social media and have been exposed to soft selling content of d'Alba products but have never made a purchase transaction. Data was collected through a five-point Likert scale questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results of the study show that the soft selling strategy based on implicit advertising has a positive and significant effect on buying interest, lifestyle, and brand image. Lifestyle and brand image have also been proven to have a positive and significant effect on buying interest, and significantly mediate the influence of implicit advertising-based soft selling strategies on buying interest. These findings confirm the importance of an implicit marketing communication approach in building lifestyle perceptions and brand image to drive buying interest in Generation Z.